Mapping And Strategies For Locale Specific-Based Poverty Alleviation In Tabanan Regency, Bali Province - Setiawina, Nyoman Djinar; Lestari, Ni Putu Nina Eka; Suidarma, I Made (Journal of Rural Indonesia [JORI], 2014)
Poverty is one of the main problems in a complx and chronic process of economic development that has no border in time and space dimension. Tabanan Regency, one of the regions with the highest poverty index among other regions has 41.894 people in poverty and Kediri sub-district has a pole position of people in poverty. One of the poverty problems to implement poverty alleviation is not optimal because the indicator does not use local specific or the root of the problem. This study aimed to analyze poverty condition in Tabanan Regency includes 1) describing real condition of poverty in Tabanan Regency with Nested Spheres of Poverty; 2) identifying the determinant of poverty in Tabanan Regency; 3) determining strategy of poverty alleviation based on local genius. The method used in this study was descriptive-quantitative using poverty index and other statistical descriptive analysis. The area of the study is ten sub-districts in Tabanan Regency: Selemadeg, Kerambitan, Tabanan, Kediri, Marga, Baturiti, Penebel, Pupuan, West Selemadeg, and East Selemadeg. The result of this study is poverty in Tabanan Regency is of moderate category for all aspect of Nested Spheres of Poverty, so poverty problem is still important program to alleviate. Aggregately, the rank priority of poverty is economic, wealth, political, natural resources, knowledge, health, social and infrastructure. The strategy to alleviate poverty in Tabanan Regency is to strengthen the economy, social culture and local institution, mitigating vulnerability of poverty, and sustainabile program for increasing the welfare of the community. Â© 2014 Journal of Rural Indonesia [JoRI] IPB. All rights reserved.Keywords: Mapping, Strategy, Poverty Alleviation, Nested Spheres of Poverty